Photography and Development of Photo Industry in Ukraine: History and Modernity (to the 180th Anniversary of Photography) - Горевалов, Сергій Іванович; Зикун, Наталія Іванівна (Київський національний університет імені Тараса Шевченка, 2020)
У статті в діахронічному аспекті із використанням методів порівняльного аналізу, систематизації, узагальнення досліджується поліпредметне явище фотографії, що виразно поєднує ознаки документа, твору мистецтва, сучасної технології й засобу комунікації. Узагальнюється інформація про тривалу історію фотографії як форми фіксування реальності, як одного із способів збереження й транслювання інформації. Окреслюється зміна функціонально-інструментальних характеристик фотографії. Вказується на швидке розширення напрямів розвитку фотосправи в багатьох українських регіонах уже наприкінці ХІХ – на початку ХХ ст.: формування інфраструктури; виникнення професійних і аматорських фототовариств і організацій, що вели активну професійну й просвітницько-популяризаторську діяльність. Доводиться, що активна фотодіяльність сформувала суспільний запит на наукове вивчення фотосправи, формування її теорії; викликала виникнення спеціалізованих періодичних фотовидань («Фото-Кіно» (1924), «Фото для всіх» (1928–1930) і «Фото – соцбудівництву» (1932–1934). Усе це сприяло зародженню системи навчання фахівців з фотосправи, формальної фотоосвіти, вивчення курсу фотографії в мистецьких закладах освіти. Простежуються передумови й перші кроки становлення фотожурналістики й формування системи фотожанрів. Констатується активна участь українських майстрів у виробництві й удосконаленні фототехніки. Йдеться про те, що в 30-х роках ХХ ст. був зроблений значний крок державної політики в розвиток заводів машинобудування, хімічної промисловості України, що створило передумови для розвитку фотоіндустрії. Значна увага приділяється основним досягненням українського виробництва фототехніки, насамперед на київському заводі «Арсенал».

In the article the multi-subject phenomenon of photography, which clearly combines the features of a document, a work of art, modern technologies and a means of communication is studied in the diachronic aspects using the methods of comparative analysis, systematization and generalization. It summarizes the information about the long history of photography as a form of fixation of reality, as a way of storing and transmitting information. The changes in functional and instrumental characteristics of photography are outlined. The rapid expansion of the direction of development of photography in many Ukrainian regions as early as the late nineteenth and in the early twentieth centuries is indicated: formation of infrastructure; emergence of professional and amateur photo societies and organizations that have been active in professional and educational and promotional activities. It is proved that active photography activity formed a public request for scientific study of photography, its theory formation; caused the emergence of specialized periodical photo editions (“Photo-Cinema” (1924), “Photo for Everyone” (1928-1930) and “Photo - Socialistic Construction” (1932-1934). All this contributed to the emergence of a system of professionals training in photography, formal photo education, study of photography in art educational institutions. The prerequisites and the first steps of formation of photojournalism and the system of photo genres are traced. The active participation of Ukrainian masters in production and improvement of photographic equipment is stated. It is said that in the 30’s of the twentieth century a significant step of state policy was made in development of the plants of mechanical engineering and chemical industry of Ukraine, which created the preconditions for development of photo industry. The considerable attention is paid to the major achievements of Ukrainian production of photographic equipment, first of all at the Kyiv Arsenal Factory.
Фотографія й становлення фотосправи в Україні: історія та сучасність (до 180-річчя фотографії)
Keywords: daguerreotype; retouch; photo; camera; photo production; photojournalism; дагеротип; ретуш; фотографія; фотоапарат; фотопродукція; фотожурналістика